EVALUATION AND SUGGESTIONS FOR IMPROVING THE SYSTEM OF TRAINING AND EDUCATION OF INDUSTRIAL PERSONNEL ON THE BASIS OF FOREIGN EXPERIENCE - Averina, Tatiana; Avdeeva, Elena; Priz, Violetta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The paper deals with the concept and essence of the concept "Industry 4.0", characterized by the digitalization of all economic activities, and its significance and components are shown. The aim of the research study is to assess the existing system of education of engineering personnel and develop proposals for its improvement in the conditions of the fourth industrial revolution. Methods of empirical and theoretical research, including SWOT analysis, are used. With a SWOT-analysis the positive and negative aspects, as well as the opportunities and threats of implementing this concept in the economic life of Russia are estimated. The priority directions of formation information infrastructure of the digital economy are given. The components of the quality of educational services are identified. The experience of foreign countries shows that digital technologies will lead to transformations in the labour market, a new model of labour and employment "Work 4.0" will be distributed, within which a new type of labour activity will be developed, called an on-demand economy etc. New requirements of employers for training of personnel for industrial enterprises are particularly considered.